2003
DOI: 10.1063/1.1607310
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum synthesis and determination of the ionization energies of different molecular orbitals for BrOBr and HOBr

Abstract: Rovibrationally selected and resolved pulsed field ionization-photoelectron study of propyne: Ionization energy and spin-orbit interaction in propyne cation J. Chem. Phys. 128, 094311 (2008) Pure BrOBr and HOBr were synthesized in vacuum by heterogeneous reactions of the dried bromine vapor and Br 2 /H 2 O mixture vapors ͑5:1͒ with HgO, respectively, and then characterized by He I photoelectron spectroscopy ͑PES͒ and augmented by ab initio GAUSSIAN 2 and the outer valence Green's functional calculations. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…The potential energy surfaces of HBrO, , HBrO 2 , , and HBrO 3 , have been explored previously, mostly with a view to atmospheric chemistry. The isomers HOBr, HOBrO, and HOBrO 2 are pertinent in the current context and molecular models are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The potential energy surfaces of HBrO, , HBrO 2 , , and HBrO 3 , have been explored previously, mostly with a view to atmospheric chemistry. The isomers HOBr, HOBrO, and HOBrO 2 are pertinent in the current context and molecular models are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…(8) and (9). However, as for the laboratory studies on its physical chemistry properties, it can be prepared through the hydrolysis of BrOBr [28] . Although many molecular structural properties of HOBr have been reported, the electronic structure in the gas phase remains unknown, due to its instability in the gas phase with high purity.…”
Section: Hobr Brobrmentioning
confidence: 99%
“…We approached this problem through the vacuum heterogeneous reaction of Br 2 /H 2 O mixture (5︰1) with activated HgO [28] . Experimental details are as follows: the evacuated flask with freshly prepared and thermally activated HgO was successively filled with bromine vapor (150 Torr) and H 2 O (30 Torr) at 30℃ in the dark.…”
Section: Hobr Brobrmentioning
confidence: 99%
“…1 The studies of bromine-containing species [2][3][4][5][6][7][8][9] are less than those of the chlorine-containing species, 3,4,10-12 although Wennberg's 13 studies have shown that catalysis involving bromine-containing species accounts for as much as 30% of the total halogen-controlled loss of the strospheric ozone in Antarctic Circle. In terms of ozone destruction, moreover, bromine-containing species is 100 times more efficient than chlorine-containing species on a mole-per-mole basis.…”
Section: Introductionmentioning
confidence: 99%